Somatic delusions and obsessive-compulsive disorder in schizophrenia - Arnold C. Lawrence; S. T. Rataemane (South African Family Practice)
This review is based on a case study of a clinical presentation of schizophrenia with somatic and olfactory delusions and obsessive-compulsive symptoms (OCS). The patient was seen at the surgical out-patient department of the Dr George Mukhari Academic Hospital, Ga-Rankuwa, complaining of a dilated anus and requesting its reduction by the doctor on duty. The patient was later referred to the psychiatry department of the same hospital and diagnosed with schizophrenia with somatic delusions and OCS according to the Diagnostic and Statistical Manual of Mental Disorders (DSM-IV) criteria. He was screened for schizophrenia, OCS and olfactory and somatic delusions by means of a systematic psychiatric interview and the administration of specific assessment scales. The diagnosis was then confirmed to be schizophrenia with olfactory and somatic delusions and obsessive-compulsive disorder (OCD) features. This presentation suggests unique ways in which schizophrenia could present, including somatic and olfactory delusions and features of OCD, which may significantly influence the functional outcome of patients. This case study highlights the importance of identification and treatment of OCD in schizophrenia.